Perancangan Model Pengukuran Kinerja Rantai Pasok Berbasis Lean dan Green menggunakan Balance Scorecard di PT. P&P Lembah Karet - Alizar Hasan; Berry Yuliandra; Eureka Perdana Putra (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2016)
Rapid technological developments helped bring an increase in the level of business competition. Competitive business strategies required to address the challenges of business competition. PT P&P Lembah Karet is a company engaged in the plantation and crumb rubber processing industry. Marketing area is scattered inside and outside the country led to the supply chain performance become one of the important issues in the company. The use of Lean and Green concept in the supply chain system can become a competitive advantage for PT. P&P Lembah Karet to create a more effective and efficient supply chain strategy in terms of expenditure and environmental impact. Performance measurement is required to determine the effectiveness and efficiency of these two concepts implementation in the supply chain companies. Performance measurement system was developed based on four perspectives of the Balanced Scorecard (BSC): financial, customer, internal business processes, learning and growth. Key Performance Indicator (KPI) which is used as a measurement basis is formulated through the concept of lean and green. The weight value of each KPI is determined using Analytical Hierarchy Process (AHP) with relevant experts as respondents. Respondents selected based on the experience and knowledge, especially experience and knowledge that relevant with the topic of this research. The weight value determined the order of KPI priority. Face validity is used to validate the performance measurement model. Data processing and analysis yielded 25 lean and green-based KPIs that are relevant to crumb rubber supply chain at PT. P&P Lembah Karet with 3 KPI for financial perspective, 4 KPI for customer perspective, 11 KPI for internal business process perspective and 7 KPI for learning and growth perspective. The structure of designed models showed that customer perspective is the most priority aspects.